235 Uterine Function During Maternal Recognition of Pregnancy Differs Due to Size of the Ovarian Reserve in Beef Heifers. (8th October 2021) - Cushman, Robert A; Rosasco, Shelby; Epperson, Kaitlin M; Northrop-Albrecht, Emmalee J; Rich, Jerica J; Chase, Chadwick; Miles, Jeremy R; Crouse, Matthew S; Perry, George A; Summers, Adam; Snider, Alexandria
Abstract: The relationship of ovarian reserve parameters to fertility in mammalian females continues to be debated. We demonstrated improved uterine function, creating an environment that is more supportive of early embryonic development in beef heifers with increased numbers of follicles. In the present study we hypothesized that timing of luteolysis differs between heifers with increased compared to heifers with diminished numbers of follicles. Angus heifers (n = 20/ group) were classified as low (14.7 ± 1.1) or high (32 ± 1.1) antral follicle number based on ovarian ultrasonography, and artificially inseminated (d0) following a Select Synch protocol. At d16 after insemination, heifers were slaughtered, and reproductive tracts collected. Tracts were flushed with 20 mL of physiological saline to determine pregnancy status by presence of a conceptus and endometrial samples from the horn ipsilateral to the CL were frozen for determination of transcript abundance. Real-time RT-PCR was performed to determine relative transcript abundance of oxytocin receptor (OXTR) and interferon-stimulated gene-15 (ISG15) with glyceraldehyde-3-phospate dehydrogenase as the endogenous reference gene. Transcript abundance was analyzed using the MIXED procedure of SAS with follicle group, pregnancy status and the interaction as fixed effects. Transcript abundance of ISG15 was greater in pregnant endometrium than non-pregnant endometrium (2.75 ± 0.25 vs 0.16 ± 0.22-fold; P < 0.0001) with no influence of follicle group or the interaction. The interaction of follicle group and pregnancy status influenced OXTR transcript abundance (P = 0.06). Luteolytic mechanisms were activated in non-pregnant heifers with diminished numbers of follicles (1.46 ± 0.25-fold) and were not activated in pregnant heifers (0.06 ± 0.22-fold) or heifers with increased numbers of follicles that were not pregnant (0.32 ± 0.30-fold). These data indicate a wider window of recognition of pregnancy in beef heifers with increased numbers of ovarian follicles. USDA is an equal opportunity provider and employer.